2010
DOI: 10.1016/j.jsv.2009.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of elastic modes propagating in multi-wire helical waveguides

Abstract: Elastic guided waves have some potential for non-destructive inspection of civil engineering multi-wire steel cables. However, wave propagation inside such structures is not yet fully understood. This paper investigates multi-wire helical waveguides with special attention to the common seven-wire strand configuration (one straight core surrounded by one layer of six helical wires).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 27 publications
6
71
0
Order By: Relevance
“…Without PML (γ=1), this expression coincides with the results standardly found for closed waveguide problems [48,49]. With PMLs, M is complex and E tot is no longer real.…”
Section: Modal Filtering Of Radiation Modessupporting
confidence: 88%
“…Without PML (γ=1), this expression coincides with the results standardly found for closed waveguide problems [48,49]. With PMLs, M is complex and E tot is no longer real.…”
Section: Modal Filtering Of Radiation Modessupporting
confidence: 88%
“…Here, to ensure low dispersion, an appropriate thickness of the wire and suitable mean -helical and conical configurations due to curvature effect were considered for selection of waveguide dimensions using our earlier approaches [17][18][21][22][23] . Studies of waves in helical waveguides are reported in literature [25][26] with applications in civil structures. The elastic wave dispersion effects were modelled for cylindrical and helix geometries using a finite element approach in a non-orthonormal coordinate system.…”
Section: Ultrasonic Waves In Stepped-helical and Conical Waveguidesmentioning
confidence: 99%
“…A straight waveguide sensor system was reported 9 for measuring the vitrification melter temperature. The guided wave behaviour was studied in different curvature structures of helical and spiral ultrasonic waveguide configurations [17][18][19][20][21][25][26] for designing the distributed temperature measurement sensor. Here, the stepped and conical waveguides are designed based on this approach for measuring the distributed temperature measurements in a high-temperature furnace.…”
Section: Introductionmentioning
confidence: 99%
“…The studies on waves in helical waveguides have been previously reported on acoustic waves, 25 electromagnetic waves 26 and elastic waves 27,28 with applications in civil structures. For avoiding dispersion effects due to curvature, the recommended helix diameter 21 is such that the ratio a of the helix diameter (D) to the torsional mode wavelength (λ T ) must be maintained above 2 as defined below:…”
Section: Helical Waveguide Designmentioning
confidence: 99%